Emotional intelligence and relation to emotional health in doctoral students in the field of science and techniques of physical and sports activities in Algeria - hamza boukhalfa; Ben Sheikh Youssef (sports creativity, 2025)
The current study aims at searching for the type of relationship between emotional intelligence and emotional health among students of scientific and technical institutes of physical and sports activities at the Algerian University،To achieve the objectives of the present study،we used the descriptive approach. Two measures of emotional intelligence and the other of emotional health were applied to a random sample، The number of 20 students and the results indicate a positive correlation between emotional intelligence and all dimensions of emotional health.